Dynamic equilibrium between insertion and excision of P elements in highly inbred lines from an M' strain of Drosophila melanogaster. - Biemont, C. (Journal of Molecular Evolution, 1994)
Six highly inbred lines of Drosophila melanogaster extracted from an M' strain (in the P/M system of hybrid dysgenesis) were studied for the evolution of the number and chromosomal location of complete and defective P elements through generations 52-200. These lines possessed full-sized P elements but differed in their cytotype (M or P). Three lines with P cytotype and full-sized P elements at site 1A had a constant P copy number over generations with low rates of insertion and excision. Three lines with M cytotype and at least one full-sized P element accumulated P copies over the generations and reached a plateau near generation 196, at which rates of transposition and excision were equal to 1.2 x 10(-3) to 3 x 10(-3) events per element per generation. At that time these three lines still presented an M cytotype, produced transposase, and were able to regulate P copy number. The similarity at equilibrium between insertion and excision rates was exactly what was expected from theoretical models for a self-regulated element. The large number of generations necessary to attain the equilibrium in copy number indicates, however, that caution may be de rigueur when testing theoretical models of copy-number containment based on transposition and excision-rate comparison.